Classifications of haemodialysis vascular access stenosis: a scoping review - Lawrie, Katerina; O'Neill, Stephen; Malik, Jan; Janousek, Libor; Corr, Michael; Maly, Stepan; Chlupac, Jaroslav; Waldauf, Petr (BMJ open, 2025)
OBJECTIVES: Vascular access (VA) stenoses play a significant role in the morbidity of the haemodialysed population. Classifications for diagnosis, assessment and proposal of treatment strategies can be useful clinical and methodological tools. This review aims to present a comprehensive summary and propose further methodological approaches. DESIGN: A systematic review of the literature, evaluating classifications for dialysis-related VA stenosis. DATA SOURCES: Web of Science, Scopus, PubMed, Google Scholar and the ClinicalTrials.gov registry were searched from inception to 7 December 2024. ELIGIBILITY CRITERIA: All articles containing classifications regarding dialysis VA were eligible, with no restrictions on the study type or language of the full text. DATA EXTRACTION AND SYNTHESIS: Two independent researchers performed the search and initial screening. Four vascular surgeons assessed the included classifications using a modified Buchbinder's critical appraisal tool to evaluate quality. RESULTS: From 4771 screened papers, 59 full-text papers were retrieved and 24 articles contained classifications. Three classifications were dedicated to VA stenosis, all based on the anatomical location of lesions. According to the modified Buchbinder's appraisal, the classifications were assessed as moderate-to-good quality. The literature disposes of immense inconsistency in terms of the definition of significant stenosis indicated for treatment. CONCLUSIONS: VA significant stenosis and its classification is a non-uniformly understood issue with many different criteria and categorisations. This basic methodological problem leads to inconsistent results. We recommend the unification of the criteria and their validation in prospective studies.
Keywords: Cardiovascular Disease; Constriction, Pathologic; End stage renal failure; arteriovenózní zkrat; Dialysis; dialýza ledvin; Vascular surgery; Vascular Access Devices; Renal Dialysis; Vascular medicine; lidé; cévní přístupy; Humans; Arteriovenous Shunt, Surgical; stenóza